Gross Anatomical Features of Mandible in Adult Guinea Pigs (Cavia porcellus) - Raja, K.; Ushakumary, S.; Rajathi; K, Kumar; Ramesh, Geetha (Indian Journal of Veterinary Anatomy, 2024)
The present study was conducted on six adult guinea pigs to investigate the gross anatomical features of mandible. Mandible is the largest bone in the skul forming the lower jaw showing the 1 incissor, 1 premolar and 3molar teeth. The Inter mandibular angle is more than 85-900. Teeth arrangement in the mandible was in converging mannar. Cheek teeth were more incline towards the buccal cavity. Mental foramen was located infront of the first check tooth on the lateral face of the horizontal rami of mandible. Mandibular foramen located more caudally on the medial face of vertical ramus of mandible. Masseteric fossa was distributed at the level of the 3rd check tooth but the pterygoid fossa is shallow but fovea is not distinct. Special feature of the mandible is sulcus ascendens of Krause which was placed lateral to the teeth which is the continuation from the coronoid process. Masseteric crest was extended from posterior aspect below the suclcus to the anterior end to form the mandibular tubercle.